A mullite oxide catalyst of SmMn2O5 for three-way catalysis: synthesis, characterization, and catalytic activity evaluation. Issue 70 (11th July 2016) - Zhao, Pengfei; Yu, Pengfei; Feng, Zijian; Chen, Rong; Jia, Liwei; Wang, Jianqiang; Shen, Meiqing; Shan, Bin
Abstract : CO conversion as a function of temperature for SMO and LCO is shown in the graphical abstract image. SMO reached 95% conversion at 150 °C and showed a better CO oxidation activity than LCO. Abstract : Mullite oxide SmMn2 O5 (SMO) was synthesized through a co-precipitation method. The CO + O2 model system and more realistic gas mixtures were evaluated, and compared with perovskite LaCoO3 (LCO), SMO showed a better reaction activity as well as a higher catalytic activity and stronger hydrothermal resistance. Characterizations including XRD, BET, SEM, XPS, H2 -TPR, O2 -TPD, and CO + O2 pulse were undertaken in order to gain insight into the origin of the SMO three-way catalytic activity. The lower adsorbed oxygen reduction temperature for SMO by H2 -TPR indicated a better reducibility. O2 -TPD suggested that SMO exhibited excellent mobility of β-oxygen species. CO + O2 pulse further revealed that the SMO catalyst had a better oxygen storage capacity than the LCO perovskite did. With a better reducibility, facile mobility of oxygen species and better oxygen storage capacity, mullite oxide SMO showed a preferable three-way catalytic activity.